El homicidio vial por el estado de embriaguez, análisis en derecho comparado entre Ecuador, España y Colombia - Guañuna Rodríguez, Johann Enrique (2025)
Vehicular homicide due to intoxication is a critical issue affecting Ecuador, with severe legal, social, and economic consequences. This article analyzes, from a comparative law perspective, the similarities and differences in the regulation and punishment of this crime in the three countries, assessing its impact on prevention and justice. Driving under the influence of alcohol is one of the leading causes of traffic accidents, with alarming figures of deaths and injuries, especially among young people, in Ecuador and worldwide. The aim was to analyze the regulation and legal treatment of vehicular homicide caused by intoxication in Ecuador, with an emphasis on comparative law between Spain and Colombia. The methodology used was mixed, with a qualitative emphasis, based on documentary analysis of regulations, doctrines, case law, and public policies. In addition, comparative, analytical-synthetic, inductive-deductive, exegesis, and statistical methods were employed to decompose and contrast the legal systems of the studied countries. The results showed that, while the sanctions were severe in all three countries, including imprisonment and license suspension, the effectiveness of these measures varied. Spain stood out for its sobriety checkpoints and educational campaigns, while Ecuador and Colombia faced challenges in implementing preventive policies. In conclusion, the need for a comprehensive approach is highlighted, combining punitive sanctions, preventive measures, and rehabilitation programs to reduce the incidence of vehicular homicides due to intoxication, thus protecting road safety and ensuring justice for the victims.